Specific nuclear proteins interact with the Rous sarcoma virus internal enhancer and share a common element with the enhancer located in the long terminal repeat of the virus. - Karnitz, L (1987)
We have documented that the Rous sarcoma virus (RSV) internal enhancer functions in the nontransformed Baby Hamster Kidney (BHK) cell line. The sequences within this region were assayed for their ability to bind to specific factors present in BHK nuclear extracts using the gel retardation assay and DNAse I footprinting. At least two sequences within the internal enhancer which can specifically bind nuclear factors in vitro have been identified. These regions are located between nucleotides 813-850 and 856-877. These sites map within the overall region of the internal enhancer which has been shown to be essential for enhancer activity and within the specific region which can function as an orientation independent enhancer. Using the DNase I footprinting and binding data to design an oligonucleotide, we have demonstrated that an oligonucleotide extending from nucleotides 804-877 will substitute efficiently as an enhancer. We also demonstrate that the SV40 enhancer does not compete for the factors which bind to the RSV internal enhancer, whereas an oligonucleotide to the binding site for EFII in the LTR can compete for factor binding to the internal enhancer.